Cu8GeSe6-based thermoelectric materials with an argyrodite structure. Issue 4 (11th January 2017) - Jiang, Binbin; Qiu, Pengfei; Eikeland, Espen; Chen, Hongyi; Song, Qingfeng; Ren, Dudi; Zhang, Tiansong; Yang, Jiong; Iversen, Bo Brummerstedt; Shi, Xun; Chen, Lidong
Abstract : Cu8 GeSe6 argyrodite-type compound is a new thermoelectric material which exhibits extremely low lattice thermal conductivity and high thermoelectric performance. Abstract : Recently, liquid-like superionic thermoelectric materials have attracted great attention due to their extremely low lattice thermal conductivity and high thermoelectric figure of merit ( ZT ). Argyrodite-type compounds are typical superionic semiconductors with two independent structural units that can be used to separately tune electrical and thermal transport properties. In this work, we report that Cu8 GeSe6 with an argyrodite structure is a new class of thermoelectric materials with extremely low lattice thermal conductivity. The presence of two independent structural units in Cu8 GeSe6 provides the possibility of greatly improving its electrical transport properties while maintaining ultralow lattice thermal conductivity. By alloying Ag and Te in Cu8 GeSe6, the ZT values are significantly improved to above unity at 800 K in Cu7.6 Ag0.4 GeSe5.1 Te0.9, comparable with the best superionic liquid-like thermoelectric materials. The ultralow thermal conductivity is mainly attributed to the weak chemical bonding between Cu atoms and the rigid [GeSe6 ] sublattice.